Quantitative trait loci associated with amino acid concentration and in vitro protein digestibility in pea (Pisum sativum L.) - Zhou, Junsheng; Wan, Zhongyang; Gali, Krishna Kishore; Jha, Ambuj Bhushan; Nickerson, Michael T.; House, James D.; Tar’an, Bunyamin; Warkentin, Thomas D. (Frontiers in Plant Science, 2023)
With the expanding interest in plant-based proteins in the food industry, increasing emphasis is being placed on breeding for protein concentration and quality. Two protein quality traits i.e., amino acid profile and protein digestibility, were assessed in replicated, multi-location field trials from 2019 to 2021 in pea recombinant inbred line population PR-25. This RIL was targeted specifically for the research of protein related traits and its parents, CDC Amarillo and CDC Limerick, had distinct variations in the concentration of several amino acids. Amino acid profile was determined using near infrared reflectance analysis, and protein digestibility was through an in vitro method. Several essential amino acids were selected for QTL analysis, including lysine, one of the most abundant essential amino acids in pea, and methionine, cysteine, and tryptophan, the limiting amino acids in pea. Based on phenotypic data of amino acid profiles and in vitro protein digestibility of PR-25 harvested in seven location-years, three QTLs were associated with methionine + cysteine concentration, among which, one was located on chromosome 2 (R2 = 17%), and two were located on chromosome 5 (R2 =11% and 16%). Four QTLs were associated with tryptophan concentration and are located on chromosome 1 (R2 = 9%), chromosome 3 (R2 = 9%), and chromosome 5 (R2 = 8% and 13%). Three QTLs were associated with lysine concentration, among which, one was located on chromosome 3 (R2 =10%), the other two were located on chromosome 4 (R2 =15% and 21%). Two QTLs were associated with in vitro protein digestibility, one each located on chromosomes 1 (R2 = 11%) and 2 (R2 = 10%). QTLs associated with in vitro protein digestibility, and methionine + cysteine concentration on chromosome 2 were identified to be co-localized with known QTL for total seed protein concentration in PR-25. QTLs associated with tryptophan and methionine + cysteine concentration co-localized on chromosome 5. The identification of QTLs associated with pea seed quality is an important step towards marker-assisted selection of breeding lines with improved nutritional quality, which will further boost the competitiveness of pea in plant-based protein markets.